Microscopic evaluation of the manholes in selected sewerage pressure system - Bogusławski, Bartosz; Głowacka, Anna; Rucińska, Teresa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the research was to determine changes in the elemental composition of concrete under the influence of exposure to hydrogen sulphide in the existing sewage system. The system operator pointed to significant problems with odours in this system. The research included a fragment of the pressure sewage system. The concentration of gases: hydrogen sulphide, ammonia and methane was measured in selected wells. High concentrations of hydrogen sulphide (over 200 ppm) were recorded in the studies.
Keywords: hydrogen sulfide; biocorrosion; pressure sewage system; sulfate attack on concret; siarkowodór; biokorozja; kanalizacja ciśnieniowa